Features of the Speech Portrait of a Modern Medical Student - Razikova Lola Tuychiyevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article is devoted to the study of the features of the speech portrait of a modern medical student. The article analyzes the lexicon of students of a medical university, an attempt is made to describe a collective speech portrait that characterizes the specifics of the future doctor's speech at the lexical and phraseological levels.